“The water is murky, the water is not moving”: qualitative water quality assessment by citizen scientists - Blanco-Ramírez, Sara; van Meerveld, Ilja; Camargo, Alejandro; Seibert, Jan (Frontiers in Water, 2025)
Numerous studies have demonstrated that citizen science can provide valuable data on physical, chemical, and biological aspects of water quality. These studies mainly used quantitative methods. Qualitative approaches have been used to describe water quality conditions for much longer, but remain largely overlooked. The color, odor, and presence of aquatic vegetation or garbage influence human perceptions of river water quality, the use of the water, and thus the relation between humans and waterbodies. Yet, few studies have assessed how visual water quality indicators and local knowledge of water quality or sources of pollution can be used in citizen science projects, despite recent studies calling for greater attention to qualitative data sources. Qualitative data can enhance the interpretation of quantitative data and deepen the understanding of human-water relations. This paper evaluates qualitative water quality descriptors collected through the citizen science smartphone app CrowdWater and analyses how citizen scientists perceive and assess water quality in the app. Our analysis not only indicates that some citizen scientists already take quantitative physical–chemical measurements of water quality (even though this is not part of the app) but also that they frequently report their perception of water quality based on visual indicators and local knowledge. Our study makes a methodological contribution to traditional approaches in citizen science and water quality studies, highlighting the need to explore less frequently used methods and data sources and less frequently studied aspects of water quality.